Long-Term Regulation of Excitation–Contraction Coupling and Oxidative Stress in Cardiac Myocytes by Pirfenidone - Monsalvo-Villegas, Adrián; Osornio-Garduño, Diana Stephanie; Avila, Guillermo (Frontiers in Physiology, 2018)
Pirfenidone (PFD) is used to treat human pulmonary fibrosis. Its administration to animals with distinct forms of cardiovascular disease results in striking improvement in cardiac performance. Here, its functional impact on cardiac myocytes was investigated. Cells were kept 1-2 d under either control culture conditions or the presence of PFD (1 mM). Subsequently, they were subjected to electrical stimulation to assess the levels of contractility and intracellular Ca2+. The PFD treatment promoted an increase in both peak contraction and kinetics of shortening and relaxation. Moreover, the amplitude and kinetics of Ca2+ transients were enhanced as well. Excitation-contraction coupling (ECC) was also investigated, under whole-cell patch-clamp conditions. In keeping with a previous report, PFD increased twofold the density of Ca2+ current (ICa). Notably, a similar increase in the magnitude of Ca2+ transients was also observed. Thus, the gain of ECC was unaltered. Likewise, PFD did not alter the peak amplitude of caffeine-induced Ca2+ release, indicating stimulation of Ca2+-induced–Ca2+-release (CICR) at constant sarcoplasmic reticulum (SR) Ca2+ load. A phase-plane analysis indicated that PFD promotes myofilament Ca2+ desensitization, which is being compensated by higher levels of Ca2+ to promote contraction. Interestingly, although the expression of the Na+/Ca2+ exchanger (NCX) was unaffected, the decay of Ca2+ signal in the presence of caffeine was 50% slower in PFD-treated cells (compared with controls), suggesting that PFD downregulates the activity of the exchanger. PFD also inhibited the production of reactive oxygen species (ROS), under both, basal conditions and the presence of oxidative insults (acetaldehyde and peroxide hydrogen). Conversely, the production of nitric oxide (NO) was either increased (in atrial myocytes) or remained unchanged (in ventricular myocytes). Protein levels of endothelial and neuronal nitric oxide synthases (eNOS and nNOS) were also investigated. eNOS values did not exhibit significant changes. By contrast, a dual regulation was observed for nNOS, which consisted of inhibition and stimulation, in ventricular and atrial myocytes, respectively. In the latter cells, therefore, an up-regulation of nNOS was sufficient to stimulate the synthesis of NO. These findings improve our knowledge of molecular mechanisms of PFD action and may also help in explaining the corresponding cardioprotective effects.